Critical realism and economic anthropology - Harvey, John; Smith, Andrew; Golightly, David (Taylor & Francis, 2017)
This paper discusses basic critical realism within the context of economic anthropology and develops an approach to studying material relations between people. A diachronic form of analysis, following the work of Bhaskar and Archer, is described as a practical means of analysing property rights. This new approach emphasises epistemic relativism and ontological realism in order to compare disparate forms of human interaction across cultures. The aim of doing this is to develop a philosophical framework that allows for the comparison of economic practices without resorting to judgemental relativism. The implications are significant for institutional economics and anthropology alike, particularly for researchers examining multiple overlapping practices such as market and gift exchange.